GAYA BAHASA PERTAUTAN DALAM NOVEL HOME SWEET LOAN KARYA ALMIRA BASTARI - Febrianti; La Yani Konisi; Saidiman (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The purpose of this study is to describe the linking language style contained in the novel Home Sweet Loan by Almira Bastari. This type of research is library research and the method used in this study is a descriptive method that aims to describe the results of the study in detail and in depth. The data used in this study is a novel text, which contains a number of linking language styles in the novel Home Sweet Loan by Almira Bastari. The data collection method is the literature review and study method. The data collection technique is the reading and note-taking technique. The data analysis technique used is the content analysis technique which is used to determine the existence of certain words, themes, or concepts in certain qualitative data (namely text). The research data shows that there is a linking language style. The linking style of language includes (1) metonymy, (2) antanaklasis, (3) symbolic, (4) synecdoche, (5) allusion, (6) euphemism, (7) dysphemism, (8) eponym, (9) antonomasia, (10) epithet, (11) erotesis, (12) parallelism, (13) ellipsis, (14) gradation, (15) asyndeton, (16) polysyndeton, (17) rhetorical, (18) interruption, (19) enumeration, (20) resentia, (21) ananculoton, (22) meiosis, (23) symmetrical. The linking style of language in the novel Home Sweet Loan can support the facts of the story and make it more interesting, followable, and memorable.